Meningkatan Hasil Belajar PAI Menggunakan Model Pembelajaran di Kelas V SDN 01 Banda Dalam - Melda Oktavia; Fitri Nefrita; Ria Kemala Sari; Desri Wahyuni; Fadhila Yusri; Adi Warman (Jurnal Pendidikan Tuntas, 2024)
Education aims to increase the quantity and quality of students. In the learning process, choosing the right learning method greatly influences the level of student learning outcomes. Learning methods are methods that can be used by educators so that the teaching and learning process runs effectively. The problem in this research is the low learning outcomes of students in Islamic Religious Education subjects. because the learning methods used are still less varied. To overcome this problem, researchers applied the Make a match method with the aim of improving PAI learning outcomes for students at UPTD SDN 01 Banda. This research used a type of classroom action research (PTK). The subjects in this research were class V students at UPTD SDN 01 Banda Dalam, totaling 10 students consisting of 4 male students and 6 female students. Classroom action research was carried out in 2 cycles, each cycle consisting of one meeting. In this research there are four stages, namely planning, implementation, observation and reflection. Data collection was carried out using observation and written tests. Based on the research results, it shows that the average student learning outcomes have increased. It is known that the KKTP score that has been determined by the school is 70. In pre-research it was discovered that 5 students had not completed it. In cycle I there was an increase of 7 students who completed. Furthermore, in cycle II there was an increase in the number of students (10) achieving a complete score with a percentage of 100%. Thus, the make a match method can improve student learning outcomes in PAI subjects at UPTD SDN 01 Inner band